When Violence Works : Postconflict Violence and Peace in Indonesia - Barron, Patrick, 1977- (Book collections on Project MUSE., 2019)
"Illuminates why postconflict areas so often continue to see violence and what can be done to consolidate peace in areas emerging from large-scale violent conflict"--